Molecular regulation of auditory hair cell death and approaches to protect sensory receptor cells and/or stimulate repair following acoustic trauma - Dinh, Christine T.; Goncalves, Stefania; Bas, Esperanza; Van De Water, Thomas R.; Zine, Azel (Frontiers in Cellular Neuroscience, 2015)
Loss of auditory sensory hair cells (HCs) is the most common cause of hearing loss. This review addresses the signaling pathways that are involved in the programmed and necrotic cell death of auditory HCs that occur in response to ototoxic and traumatic stressor events. The roles of inflammatory processes, oxidative stress, mitochondrial damage, cell death receptors, members of the mitogen-activated protein kinase (MAPK) signal pathway and pro- and anti-cell death members of the Bcl-2 family are explored. The molecular interaction of these signal pathways that initiates the loss of auditory HCs following acoustic trauma is covered and possible therapeutic interventions that may protect these sensory HCs from loss via apoptotic or non-apoptotic cell death are explored.